2017
DOI: 10.1165/rcmb.2017-0096st
|View full text |Cite
|
Sign up to set email alerts
|

An Official American Thoracic Society Workshop Report: Use of Animal Models for the Preclinical Assessment of Potential Therapies for Pulmonary Fibrosis

Abstract: Numerous compounds have shown efficacy in limiting development of pulmonary fibrosis using animal models, yet few of these compounds have replicated these beneficial effects in clinical trials. Given the challenges associated with performing clinical trials in patients with idiopathic pulmonary fibrosis (IPF), it is imperative that preclinical data packages be robust in their analyses and interpretations to have the best chance of selecting promising drug candidates to advance to clinical trials. The American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
281
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(288 citation statements)
references
References 127 publications
7
281
0
Order By: Relevance
“…Idiopathic pulmonary fibrosis is a chronic progressive interstitial lung disease of unknown origin which leads rapidly to death. Currently, BLM‐induced pulmonary fibrosis is the most classic model for exploring the pathogenesis of IPF and testing the effectiveness of new antifibrotic drugs . Recent studies have shown the mechanism of bleomycin‐induced pulmonary fibrosis: ANXA2(membrane‐associated protein A2) is a specific bleomycin target, and bleomycin binding with ANXA2 blocks TFEB (transcription factor EB)induced autophagic flux and further promotes apoptosis of epithelial cells, leading to pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 68%
“…Idiopathic pulmonary fibrosis is a chronic progressive interstitial lung disease of unknown origin which leads rapidly to death. Currently, BLM‐induced pulmonary fibrosis is the most classic model for exploring the pathogenesis of IPF and testing the effectiveness of new antifibrotic drugs . Recent studies have shown the mechanism of bleomycin‐induced pulmonary fibrosis: ANXA2(membrane‐associated protein A2) is a specific bleomycin target, and bleomycin binding with ANXA2 blocks TFEB (transcription factor EB)induced autophagic flux and further promotes apoptosis of epithelial cells, leading to pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 68%
“…RNA-seq data, importantly, show suppression of the adaptive immune response, T-cell differentiation and activation, and cytokine production by MIA-602 in bleomycin-treated mouse lungs. The effects of the GHRH-R antagonist we observe have implications for fibrosing lung diseases in humans, and they could, importantly, reveal novel pathways amenable to clinical drug development [29]. …”
Section: Discussionmentioning
confidence: 99%
“…There has been significant debate about the usefulness of animal models for IPF research, but they do represent well-characterized models of the evolution of fibrosis from injury to acute inflammation to chronic inflammation and ECM deposition [94]. Furthermore, an American Thoracic Society working group recommended that the bleomycin model be used as an important tool for the preclinical testing of anti-fibrotic agents [95]. With that context, two previous studies have noted that periostin accumulates in the lungs of both Balb/c and C57Bl/6 mice treated with bleomycin [20,96].…”
Section: Introductionmentioning
confidence: 99%